25% tannic acid solution for the relief of cervical dentin hypersensitivity - Manalo, Theresa
Tannic acid (25%) has been found to be effective in the removal of the dentinal smear layer and that it constricts the orifices of the dentinal tubules exposed by attrition, abrasion and erosion. The purpose of this study was to evaluate the effectiveness of 25% tannic acid on the reduction of cervical dentin hypersensitivity. Seven patients were tested, having at least one tooth with CDH, provided that the tooth has no carious lesion and restoration on involved surface. Application of tannic acid was done by swabbing the solution on the affected surface with the use of cotton pellets. Before and after application of the solution, each tooth was clinically tested by running the tip of an explorer on the surface of the tooth and with an air blast. After a week, the tests were repeated to check the long term effects of the tannic acid application. A significant decrease in degree of hypersensitivity was noted in majority of the patients.
Keywords: Tannic acid; Cervical dentin hypersensitivity